Idræt og politik. Niels Bukh i Østen, 1931 - Bonde, Hans (Forum for Idræt, 2000)
Artiklen gennemgår gymnastikpædagogens Niels Bukhs udenlandsrejser og internationale gennembrud, som det tog sig ud ud i 1930'erne, og fokuserer særligt på rejsen til Japan og Bukhgymnastikkens betydning for den japanske (skole)idræt. Sport and Politics – Niels Bukh in the East (1931) With his tour of the world in 1931, the Danish teacher of gymnastics, Niels Bukh, secured his reputation both at home and abroad as one of the great figures of his country, – a picture supported by the Danish Foreign Office regardless of the government’s political alignment. Bukh’s group was received by the highest ranking representatives of the Japanese occupying forces in Manchuria and Korea and became a part of Japanese propaganda in the region. The fact that Bukh’s gymnasts performed in Shenyang, the capital of Manchuria, shortly before the invasion may have been a small contribution to the attempt on the part of the Japanese military to persuade the Chinese that all was quiet on that front. Niels Bukh’s long performance tour of Japan was a triumph for him and undoubtedly also acted as a meeting point for a Japanese population which was looking for fellowship in the throes of the anxieties, not to say the passions, of war. The spread of Bukh’s gymnastics in Japanese school P.E. programmes of the 1930’s can be seen in the context of the government’s view that they constituted an efficient form of P.E. in the militarisation of youth which culminated in the escalation of the war against China in 1937 and the attack on Pearl Harbour on 7th December, 1941. Japan was the country in which Niels Bukh’s system of gymnastics became most widespread, – a fact which can be attested in Japan to this very day. Surprisingly enough, Danish gymnastics have probably made a greater quantitative contribution to Japanese physical culture than vice versa.